Repeatability of MRI for radiotherapy planning for pelvic, brain, and head and neck malignancies - Heinke, Monique Y.; Holloway, Lois; Rai, Robba; Vinod, Shalini K. (Frontiers in Physics, 2022)
Objectives: The objective of this study was to assess the repeatability of MRI for the purpose of radiotherapy treatment planning by considering the difference in registering MRI to MRI compared to registering CT and MRI. Methods: Fifty patients undergoing radiotherapy planning for gynaecological, prostate, rectal, head and neck and CNS malignancies had a planning CT followed by two T2-weighted MRIs. Anatomical landmarks were contoured on each dataset and the images were rigidly registered. Centre of Mass (COM), Dice Similarity Coefficient (DSC), and Mean Distance to Agreement (MDA) were calculated to assess structure volume and position comparing CT-MRI and MRI-MRI. Results: DSC and MDA demonstrated more consistency in delineated volumes for MRI-MRI than for the CT-MRI comparison. The median DSC values were ≥0.8 for 15 of 46 contoured structures for the CT-MRI comparison and 21 of 23 structures for the MRI-MRI comparison. MDA values were ≤1 mm for 11 of 46 structures for the CT-MRI comparison and 18 of 23 structures for the MRI-MRI comparisons. COM were also more consistent between MRI-MRI than between CT-MRI. Conclusions: There was less variability of anatomical structures between repeated MRIs than registered CT and MRI datasets, demonstrating consistency of MRI for volume delineation in radiotherapy planning.